2015
DOI: 10.1167/iovs.14-15854
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuronal Nitric Oxide Synthase in Regulating Retinal Blood Flow During Flicker-Induced Hyperemia in Cats

Abstract: The current results suggested that increased RBF in response to flicker stimulation may be mediated by nitric oxide (NO) production via nNOS activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
2
23
1
Order By: Relevance
“…36 Recently, we reported that L-NPA (5 mM), a selective nNOS inhibitor, reduced flicker-induced increases in RBF by a third of the baseline value in cats, meaning that two-thirds of the flicker-induced hyperemia is generated by NO by nNOS in neuronal and/or glial cells in the retina. 26 The current study confirmed that LAA (60 mM) as a gliotoxic compound reduced flicker-induced increases in the RBF by a third of the baseline value, indicating that two-thirds of the flicker-induced hyperemia is generated by the retinal glial cells. In addition, a flicker- The mean densities of GFAP expression in astrocytes were compared quantitatively between two groups.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…36 Recently, we reported that L-NPA (5 mM), a selective nNOS inhibitor, reduced flicker-induced increases in RBF by a third of the baseline value in cats, meaning that two-thirds of the flicker-induced hyperemia is generated by NO by nNOS in neuronal and/or glial cells in the retina. 26 The current study confirmed that LAA (60 mM) as a gliotoxic compound reduced flicker-induced increases in the RBF by a third of the baseline value, indicating that two-thirds of the flicker-induced hyperemia is generated by the retinal glial cells. In addition, a flicker- The mean densities of GFAP expression in astrocytes were compared quantitatively between two groups.…”
Section: Discussionsupporting
confidence: 79%
“…We showed previously that increases in RBF during flicker stimulation were attenuated after intravitreal injection of L-NPA (5 mM), a selective neuronal NO synthase (nNOS) inhibitor, 26 suggesting that nNOS contributes to regulation of the retinal circulation during flicker stimulation. To determine whether the decrease in RBF in response to flicker stimulation in LAA (60 mM)-treated eyes resulted from reduced NO by nNOS in retinal glial cells, we measured the RBF in response to flicker stimulation in LAA (60 mM)-treated eyes 2 hours after intravitreal L-NPA injection (5 mM).…”
Section: Effects Of a Neuronal No Synthase Inhibitor In Laa-treated Eyesmentioning
confidence: 99%
See 3 more Smart Citations